A case report of ivabradine used for heart rate control of atrial fibrillation in acute decompensated heart failure. Issue 2 (17th February 2022) - Hardison, Edward; Cox, Zachary L; Heckman, Katherine; Kelly, Patricia A; Lindenfeld, JoAnn
Abstract: Background: Achieving pharmacologic rate control in patients with atrial fibrillation (AF) with rapid ventricular response (RVR) can be tricky when the patient's underlying cardiac function is decreased. We present a case illustrating how ivabradine can be useful in this clinical scenario. Case summary: A 95-year-old woman with a history of systolic heart failure (HF) presented with acute decompensated HF in AF with RVR. Beta blockade and calcium channel blockade were avoided given her cardiac history, and diuresis with high doses of furosemide was ineffective. Her ventricular response slowed with ivabradine, allowing for rapid decongestion and a safe discharge home. Discussion: Ivabradine acts on the I f current of cardiac pacemaker cells to slow heart rate (HR), and it currently carries a class IIa recommendation to reduce the risk of HF hospitalization and cardiac death in patients with left ventricular ejection fraction ≤35% and a symptomatic HR ≥70 b.p.m. Although current recommendations are for patients in sinus rhythm, ivabradine has a theoretical benefit in patients with AF given its mechanism of action. Because it does not negatively affect inotropy or blood pressure, ivabradine was used in our patient with a good clinical outcome. Our case provides an example of ivabradine's usefulness in patients with AF in RVR with a history of depressed systolic function.